Wallet wars or digital public infrastructure? Orchestrating a digital identity data ecosystem from a government perspective - Konrad Degen; Timm Teubner (Electronic Markets, 2024)
Abstract With the eIDAS 2.0 legislation, the European Union seeks to establish a digital identity data ecosystem and to empower citizens to manage digital credentials from various sources through an ID wallet interface. To achieve this, governments must develop holistic orchestration models integrating technical, regulatory, and economic perspectives. This approach will foster ecosystem value creation, address orchestration tensions, and design sustainable operating models for various ecosystem actors. While IS research has explored private-sector governance mechanisms in platform and data ecosystems, a research gap exists in understanding public–private orchestration where governments act as orchestrators. We address this through a structured document analysis of 80 position papers from various stakeholders participating in a public government consultation process and 14 semi-structured in-depth interviews. By examining ecosystem value creation mechanisms, orchestration tensions, and monetization challenges, we identify two government orchestration standard types for the ID wallet provision. The Government ID-Infrastructure Wallet model embodies an ecosystem-integrated public infrastructure, while the Trust ID Wallet Federation exemplifies a dynamic and competition-driven approach. By bridging the self-sovereign identity ecosystem paradigm with digital identity infrastructure research, our work contributes to the understanding and theoretical development of data ecosystems and digital identity research from a government perspective.
Keywords: 330; Data ecosystems governance; Open government data; Government ecosystem orchestration; Digital identity infrastructure; Self-sovereign identity (SSI); Digital identity ecosystem